Film-forming material for lithography, film-forming composition for lithography, underlayer film for lithography, pattern formation method, and purification method

By using resin materials with polybenzene diazapine structure, the problems of insufficient solubility, thermal stability and dry corrosion stability of the material during the wet treatment process in the prior art are solved, and efficient development of microelectronic manufacturing materials is achieved.

JP7666322B2Active Publication Date: 2025-04-22MITSUBISHI GAS CHEM CO INC
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
JP2021507392
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-19
Filing Date
2020-03-18
Publication Date
2025-04-22
Estimated Expiration
2040-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high solvent solubility, thermal stability and dry corrosion stability during wet treatment, and the development of new materials is not sufficient to meet the needs of advanced microelectronic devices.

Method used

A resin material containing a polymer with a specific structure, specifically a polybenzimidazole structure, is used to form a thin film material suitable for wet treatment and advanced microelectronics manufacturing by combining with solvents and possible crosslinking agents, accelerators, etc.

Benefits of technology

It achieves high solvent solubility, thermal stability and dry corrosion stability applied in wet treatment process, meeting the needs of high-performance materials for advanced microelectronic equipment manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666322000001
    Figure 0007666322000001
  • Figure 0007666322000002
    Figure 0007666322000002
  • Figure 0007666322000003
    Figure 0007666322000003
Patent Text Reader

Abstract

This film forming material for lithography contains a resin that has the polybenzimidazole structure represented in formula (1). Y and Z are each a simple bond, a divalent linking group containing a chalcogen atom, a divalent linking group derived from a compound selected from aromatic compounds, etc., the R1s are independently a hydrogen atom or a substituent T selected from the group consisting of a specific alkyl group, a halogen atom, a nitro group, an amino group, a cyano group, a carboxylic acid group, a thiol group and a hydroxy group, the aforementioned alkyl group optionally contains an ether bond, a ketone bond, an ester bond or a urethane bond, R2 is a substituent T, m is an integer 0-3, and n is an integer 1-10000.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a film-forming material for lithography, a film-forming composition for lithography containing the material, an underlayer film for lithography formed using the composition, and a pattern formation method (e.g., a resist pattern method or a circuit pattern method) using the composition. [Background technology]

[0002] In the manufacture of semiconductor devices, microfabrication is carried out by lithography using photoresist materials. In recent years, with the increasing integration and speed of LSIs, further miniaturization by pattern rules is required. In the lithography using light exposure, which is currently used as a general-purpose technology, the essential resolution limit derived from the wavelength of the light source is approaching.

[0003] The light source for lithography used in forming a resist pattern has been shortened from KrF excimer laser (248 nm) to ArF excimer laser (193 nm). However, as the resist pattern becomes finer, problems such as resolution problems or the resist pattern collapsing after development arise, so that it is desirable to make the resist thinner. However, simply making the resist thinner makes it difficult to obtain a resist pattern with a film thickness sufficient for substrate processing. Therefore, a process has become necessary in which not only the resist pattern but also a resist underlayer film is formed between the resist and the semiconductor substrate to be processed, and this resist underlayer film also functions as a mask during substrate processing.

[0004] Currently, various resist underlayer films for such processes are known. For example, unlike conventional resist underlayer films with a high etching rate, a material for forming an underlayer film for multilayer resist processes containing a resin component having at least a substituent that generates a sulfonic acid residue by detaching an end group when a certain energy is applied and a solvent has been proposed as a material for realizing a resist underlayer film for lithography having a dry etching rate selectivity close to that of a resist (see Patent Document 1). In addition, a resist underlayer film material containing a polymer having a specific repeating unit has been proposed as a material for realizing a resist underlayer film for lithography having a dry etching rate selectivity smaller than that of a resist (see Patent Document 2). Furthermore, a resist underlayer film material containing a polymer obtained by copolymerizing a repeating unit of acenaphthylenes and a repeating unit having a substituted or unsubstituted hydroxyl group has been proposed as a material for realizing a resist underlayer film for lithography having a dry etching rate selectivity smaller than that of a semiconductor substrate (see Patent Document 3).

[0005] On the other hand, as a material having high etching resistance in this type of resist underlayer film, an amorphous carbon underlayer film formed by CVD using methane gas, ethane gas, acetylene gas, or the like as a raw material is well known.

[0006] The present inventors have also proposed an underlayer film-forming composition for lithography that contains a naphthalene formaldehyde polymer containing specific structural units and an organic solvent, as a material that has excellent optical properties and etching resistance, is soluble in a solvent, and is applicable to wet processes (see Patent Documents 4 and 5).

[0007] As for the method of forming the intermediate layer used in forming the resist underlayer film in the three-layer process, for example, a method of forming a silicon nitride film (see Patent Document 6) and a method of forming a silicon nitride film by CVD (see Patent Document 7) are known. In addition, as the intermediate layer material for the three-layer process, a material containing a silsesquioxane-based silicon compound is known (see Patent Documents 8 and 9). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2004-177668 A [Patent Document 2] JP 2004-271838 A [Patent Document 3] JP 2005-250434 A [Patent Document 4] International Publication No. 2009 / 072465 [Patent Document 5] International Publication No. 2011 / 034062 [Patent Document 6] JP 2002-334869 A [Patent Document 7] International Publication No. 2004 / 066377 [Patent Document 8] JP 2007-226170 A [Patent Document 9] JP 2007-226204 A Summary of the Invention [Problem to be solved by the invention]

[0009] As described above, numerous film-forming materials for lithography have been proposed to date, but none of them combine high levels of heat resistance and etching resistance in addition to high solvent solubility that allows the use of wet processes such as spin coating and screen printing, and the development of new materials is required.

[0010] The present invention has been made in consideration of the above-mentioned problems, and an object of the present invention is to provide a film-forming material for lithography that is applicable to a wet process and is useful for forming a film for lithography that has excellent heat resistance and etching resistance, a film-forming composition for lithography that contains the material, and an underlayer film for lithography and a pattern formation method that use the composition. [Means for solving the problem]

[0011] As a result of intensive research into solving the above problems, the present inventors have found that the above problems can be solved by using a compound having a specific structure, and have completed the present invention. That is, the present invention is as follows. [1] A film-forming material for lithography, comprising a resin having a polybenzimidazole structure represented by formula (1) described below. [2] R in the above formula (1) 1 is a group other than a hydrogen atom. [3] The film-forming material for lithography according to [1] or [2], wherein Y in the formula (1) is a single bond, -O-, -S-, -CH2-, -C(CH3)2-, -CO-, -SO2-, -C(CF3)2-, -CONH- or -COO-. [4] The film-forming material for lithography according to [3], wherein Y in the formula (1) is a single bond. [5] The film-forming material for lithography according to any one of [1] to [4], wherein the film for lithography is an underlayer film for lithography. [6] A film-forming composition for lithography, comprising the film-forming material for lithography according to any one of [1] to [5] and a solvent. [7] The film-forming composition for lithography according to [6], further comprising a crosslinking agent. [8] The film-forming composition for lithography according to [7], further comprising a crosslinking accelerator. [9] The film-forming composition for lithography according to any one of [6] to [8], further comprising a radical polymerization initiator.

[10] The film-forming composition for lithography according to any one of [6] to [9], further comprising an acid generator.

[11] An underlayer film for lithography formed using the film-forming composition for lithography according to any one of [6] to

[10] .

[12] forming an underlayer film on a substrate using the film-forming composition for lithography according to any one of [6] to

[10] ; forming at least one photoresist layer on the underlayer film; and exposing predetermined areas of the photoresist layer to radiation and developing; A method for forming a resist pattern comprising the steps of:

[13] forming an underlayer film on a substrate using the film-forming composition for lithography according to any one of [6] to

[10] ; forming an intermediate layer film on the underlayer film using a resist intermediate layer film material containing silicon atoms; forming at least one photoresist layer on the intermediate layer film; irradiating predetermined areas of the photoresist layer with radiation and developing to form a resist pattern; a step of etching the intermediate layer film using the resist pattern as a mask; a step of etching the underlayer film using the obtained intermediate layer film pattern as an etching mask; and a step of forming a pattern on the substrate by etching the substrate using the obtained underlayer film pattern as an etching mask; A pattern forming method comprising the steps of:

[14] A step of dissolving the film-forming material for lithography according to any one of [1] to [5] in a solvent to obtain an organic phase; a first extraction step of contacting the organic phase with an acidic aqueous solution to extract impurities in the film-forming material for lithography; Including, The method of purifying said forming material, wherein said solvent comprises a solvent that is optionally immiscible with water.

[15] A resin having a polybenzimidazole structure represented by formula (1') described below.

[16] Preparing a composition containing a resin having a polybenzimidazole structure; and The composition is placed on a substrate and baked at 300 to 900°C. A method for producing a film for lithography. Effect of the Invention

[0012] According to the present invention, it is possible to provide a film-forming material for lithography, which is useful for forming a film for lithography to which a wet process can be applied and which has excellent heat resistance and etching resistance, a film-forming composition for lithography containing the material, and an underlayer film for lithography and a pattern forming method using the composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, embodiments of the present invention will be described. The following embodiments are examples for explaining the present invention, and the present invention is not limited to these embodiments. In the present invention, X to Y include the end values ​​X and Y. The "composition for forming a film for lithography" is a material capable of forming a film for lithography on a substrate, which contains a resin having a polybenzimidazole structure and a solvent and has flowability capable of forming a film. The term "film-forming material for lithography" refers to a material that constitutes a film for lithography, and in one embodiment, is a resin composition that contains only a resin having a polybenzimidazole structure as a resin, and in another embodiment, is a resin composition that contains a resin having a polybenzimidazole structure as a resin and a resin other than the above resin that can form a matrix.

[0014] [Film-forming materials for lithography] <Resin> The film-forming material for lithography, which is one embodiment of the present invention, contains a resin having a polybenzimidazole structure. The resin having a polybenzimidazole structure refers to a resin (homopolymer) whose repeating unit is composed only of a unit having a benzimidazole skeleton (hereinafter also referred to as "BI unit"), or a resin (copolymer) composed of a BI unit and other units. If the amount of BI unit is large, the heat resistance of the material is improved. From this viewpoint, the lower limit of the BI unit in the latter resin is preferably 50 mol% or more, more preferably 75 mol% or more, and even more preferably 90 mol% or more, and the upper limit is preferably 99 mol% or less, more preferably 95 mol% or less.

[0015] The content of the resin having a polybenzimidazole structure in the film-forming material for lithography of the present embodiment is preferably 5 to 100 mass%, more preferably 51 to 100 mass%, even more preferably 60 to 100 mass%, even more preferably 70 to 100 mass%, and particularly preferably 80 to 100 mass% from the viewpoint of heat resistance. Resin components other than the resin having a polybenzimidazole structure in the film-forming material are not particularly limited, but include highly heat-resistant polymers such as engineering plastics.

[0016] Resins having a polybenzimidazole structure include oligomers and polymers having a benzimidazole skeleton in the side chain, and oligomers and polymers having a benzimidazole skeleton in the main chain.

[0017] The resin having a polybenzimidazole structure that can be used in the film-forming material for lithography of this embodiment can have a wide range of intrinsic viscosity depending on its structure, molecular weight, etc., but in the present invention, the number average molecular weight of the resin having a polybenzimidazole structure is generally 2,000 to 1,000,000, preferably 2,000 to 300,000, and more preferably 5,000 to 100,000.

[0018] A preferred polybenzimidazole structure in the present invention is represented by the following formula:

[0019] [ka]

[0020] In formula (1), n ​​is the number of repetitions and is an integer of 1 to 10,000, but from the viewpoint of coatability and thickness control by a wet process, it is preferably 1 to 100. Furthermore, Y and Z each are a single bond, a divalent linking group containing a chalcogen atom, and a divalent linking group derived from a compound selected from the group consisting of an aromatic compound, a linear, branched or cyclic aliphatic compound, and a heterocyclic compound.

[0021] A chalcogen atom is an atom belonging to Group 16 of the periodic table, and is preferably an oxygen atom or a sulfur atom in terms of availability of raw materials, etc. Examples of a divalent linking group containing a chalcogen atom include -O-, -S-, -CO-, -SO2-, -CONH-, and -COO-.

[0022] The divalent linking group derived from an aromatic compound is a group obtained by removing two hydrogen atoms from the compound. The compound is a monocyclic aromatic compound or a polycyclic aromatic compound having 6 to 20 carbon atoms, preferably 6 to 15 carbon atoms. In the present invention, the polycyclic aromatic compound includes a polycyclic compound in which aromatic rings are condensed with each other and a polycyclic compound in which an aromatic ring is condensed with an alicyclic ring. Examples of the group include a diphenylene group, a naphthylene group, and a trimethylindanylene group.

[0023] The divalent linking group derived from a linear, branched or cyclic aliphatic compound is a group obtained by removing two hydrogen atoms from the compound, and may contain a halogen atom. The compound includes saturated and unsaturated hydrocarbons having 1 to 10 carbon atoms. Examples of such groups include a methylene group, -CH2-, -C(CH3)2-, -C(CF3)2-, an amylene group, an octamethylene group, and a cyclohexenyl group.

[0024] A divalent linking group derived from a heterocyclic compound is a group obtained by removing two hydrogen atoms from the compound. The compound is a monocyclic or polycyclic heteroatom-containing aromatic compound having 6 to 20 carbon atoms, preferably 6 to 15 carbon atoms. Examples of the heteroatom include an oxygen atom, a sulfur atom, and a nitrogen atom. Examples of the group include a furylene group.

[0025] From the viewpoint of availability of raw materials, etc., Y is preferably a single bond, -O-, -S-, -CH2-, -C(CH3)2-, -CO-, -SO2-, -C(CF3)2-, -CONH- or -COO-, and more preferably a single bond. Therefore, in one embodiment, the structural formula is preferably represented by formula (2), and more preferably represented by formula (3).

[0026] [ka]

[0027] In formula (2), A is a single bond, -O-, -S-, -CH2-, -C(CH3)2-, -CO-, -SO3-, -C(CF3)3-, -CONH- or -COO-.

[0028] R in the above formula 1 are each independently a hydrogen atom or a substituent T. The substituent T is selected from the group consisting of an alkyl group having 1 to 30 carbon atoms which may have a substituent, an aryl group having 6 to 40 carbon atoms which may have a substituent, an aralkyl group having 7 to 40 carbon atoms which may have a substituent, an alkenyl group having 2 to 30 carbon atoms which may have a substituent, an alkynyl group having 2 to 30 carbon atoms which may have a substituent, an arylalkenyl group having 7 to 40 carbon atoms which may have a substituent, an alkoxy group having 1 to 30 carbon atoms which may have a substituent, a halogen atom, a nitro group, an amino group, a cyano group, a carboxylic acid group, a thiol group, and a hydroxyl group. The aryl group, the aralkyl group, the alkenyl group, the alkynyl group, and the arylalkenyl group may contain an ether bond, a ketone bond, an ester bond, or a urethane bond. R 2 are each independently a substituent T.

[0029] The alkyl group having 1 to 30 carbon atoms is not particularly limited, and examples thereof include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, an i-butyl group, a t-butyl group, a cyclopropyl group, a cyclobutyl group, etc. When the alkyl group having 1 to 30 carbon atoms has a substituent, it is preferable that the alkyl group is bonded with at least one type of substituent selected from the group consisting of a halogen atom, a nitro group, an amino group, a thiol group, a hydroxyl group, an epoxy group, and a group in which the hydrogen atom of a hydroxyl group is substituted with an acid dissociable group.

[0030] The acid dissociable group refers to a group that can be cleaved in the presence of an acid to generate an alkali-soluble group. The alkali-soluble group is not particularly limited, but examples thereof include a phenolic hydroxyl group, a carboxyl group, a sulfonic acid group, and a hexafluoroisopropanol group. Among them, from the viewpoint of the availability of an introduction reagent, a phenolic hydroxyl group and a carboxyl group are preferred, and a phenolic hydroxyl group is more preferred. In order to enable highly sensitive and high-resolution pattern formation, it is preferable that the acid dissociable group has a property of undergoing a chain cleavage reaction in the presence of an acid. The acid dissociable group is not particularly limited, but can be appropriately selected from those proposed in, for example, hydroxystyrene resins and (meth)acrylic acid resins used in chemically amplified resist compositions for KrF and ArF. Specific examples of the acid dissociable group include groups described in International Publication No. WO 2016 / 158168. As the acid-dissociable group, a 1-substituted ethyl group, a 1-substituted-n-propyl group, a 1-branched alkyl group, a silyl group, an acyl group, a 1-substituted alkoxymethyl group, a cyclic ether group, an alkoxycarbonyl group, an alkoxycarbonylalkyl group, and the like, which have the property of being dissociated by an acid, are preferred.

[0031] In addition to the above, the substituent that the alkyl group having 1 to 30 carbon atoms may have may be a cyano group, an acyl group, an alkoxycarbonyl group, an alkyloyloxy group, an aryloyloxy group, or an alkylsilyl group.

[0032] The aryl group having 6 to 40 carbon atoms is not particularly limited, and examples thereof include a phenyl group, a naphthalene group, a biphenyl group, etc. When the aryl group having 6 to 40 carbon atoms has a substituent, it is preferable that one or more of the above-mentioned substituents are bonded to the aryl group.

[0033] The aralkyl group having 7 to 40 carbon atoms is not particularly limited, and examples thereof include a benzyl group, a naphthylmethyl group, a biphenylmethyl group, etc. When the aralkyl group having 7 to 40 carbon atoms has a substituent, it is preferable that at least one type of substituent selected from the above-mentioned group of substituents is bonded to the aralkyl group.

[0034] The alkenyl group is an aliphatic hydrocarbon group having a carbon-carbon double bond, for example, a group represented by the following formula:

[0035] [ka]

[0036] In formula (X-9-1), R X9A , R X9B and R X9C are each independently a hydrogen atom or a monovalent hydrocarbon group having 1 to 20 carbon atoms.

[0037] The alkenyl group having 2 to 30 carbon atoms is not particularly limited, and examples thereof include a propenyl group, a butenyl group, a group having an allyl group, a group having a (meth)acryloyl group, a group having an epoxy (meth)acryloyl group, a group having a urethane (meth)acryloyl group, etc. When the alkenyl group having 2 to 30 carbon atoms has a substituent, it is preferable that one or more of the above-mentioned substituents are bonded to the alkenyl group.

[0038] The group having an allyl group is not particularly limited, but examples thereof include a group represented by the following formula (X-1): In formula (X-1), n X1 is an integer from 1 to 5.

[0039] [ka]

[0040] The group having a (meth)acryloyl group is not particularly limited, but examples thereof include a group represented by the following formula (X-2): X2 is an integer from 1 to 5, and R X is a hydrogen atom or a methyl group.

[0041] [ka]

[0042] The epoxy (meth)acryloyl group refers to a group generated by the reaction of an epoxy group with a (meth)acrylate. The group having an epoxy (meth)acryloyl group is not particularly limited, but examples thereof include a group represented by the following formula (X-3). In formula (X-3), n x3 is an integer from 0 to 5, and R X is a hydrogen atom or a methyl group.

[0043] [ka]

[0044] The group having a urethane (meth)acryloyl group is not particularly limited, but examples thereof include a group represented by the following formula (X-4). In the general formula (X-4), n x4 is an integer from 0 to 5, s is an integer from 0 to 3, and R X is a hydrogen atom or a methyl group.

[0045] [ka]

[0046] The alkynyl group is an aliphatic hydrocarbon group having a carbon-carbon triple bond, and is not particularly limited to, for example, a group represented by the following formula:

[0047] [ka]

[0048] In formulas (X-9-2) and (X-9-3), R X9D , R X9E and R X9F are each independently a hydrogen atom or a monovalent hydrocarbon group having 1 to 20 carbon atoms.

[0049] The alkynyl group having 2 to 30 carbon atoms is not particularly limited, but examples thereof include a propynyl group, a butynyl group, and a group represented by the following formula (X-8). In formula (X-8), n x8 is an integer from 1 to 5.

[0050] [ka]

[0051] When the alkynyl group having 2 to 30 carbon atoms has a substituent, it is preferable that one or more of the above-mentioned substituents are bonded to the alkynyl group.

[0052] The arylalkenyl group having 7 to 40 carbon atoms which may have a substituent is not particularly limited, and examples thereof include a vinylphenyl group, etc. When the arylalkenyl group having 7 to 40 carbon atoms has a substituent, it is preferable that one or more of the above-mentioned substituents are bonded to the arylalkenyl group.

[0053] The alkoxy group having 1 to 30 carbon atoms is not particularly limited, and examples thereof include a methoxy group, an ethoxy group, a propoxy group, a cyclohexyloxy group, a phenoxy group, a naphthaleneoxy group, a biphenyloxy group, etc. When the alkoxy group having 1 to 30 carbon atoms has a substituent, it is preferable that at least one type of substituent selected from the above-mentioned group of substituents is bonded to the alkoxy group.

[0054] From the viewpoint of availability of raw materials, it is preferable that Z is at least one group selected from the group consisting of an aromatic group having 6 to 20 carbon atoms which may have a substituent, an aliphatic group having 1 to 20 carbon atoms which may have a substituent, and an alicyclic group having 3 to 12 carbon atoms which may have a substituent. It is more preferable that Z is an aromatic group having 6 to 20 carbon atoms or an alicyclic group having 3 to 12 carbon atoms.

[0055] Such groups include, for example: Phenylene groups such as a 1,4-phenylene group and a 1,3-phenylene group; divalent condensed polycyclic aromatic groups such as naphthalene-1,4-diyl, naphthalene-1,5-diyl, naphthalene-2,6-diyl, and naphthalene-2,7-diyl groups, anthracene-1,4-diyl, anthracene-1,5-diyl, anthracene-1,8-diyl, anthracene-1,10-diyl, and anthracene-2,6-diyl groups, and phenanthrene-1,8-diyl, phenanthrene-2,7-diyl, phenanthrene-3,6-diyl, and phenanthrene-9,10-diyl groups;

[0056] divalent cyclic hydrocarbon groups such as cyclopropane-1,2-diyl, cyclobutane-1,2-diyl, cyclobutane-1,3-diyl, cyclopentane-1,2-diyl, cyclopentane-1,3-diyl, cyclohexane-1,4-diyl, decalin-1,4-diyl, decalin-1,5-diyl, decalin-2,6-diyl, decalin-2,7-diyl, norbornane-1,4-diyl, norbornane-2,3-diyl, and norbornane-2,7-diyl;

[0057] Divalent spirohydrocarbon groups such as a spiro[3,3]heptane-2,6-diyl group, a spiro[4,4]nonane-2,7-diyl group, a spiro[5,5]undecane-3,9-diyl group, and a tetracyclododecene-2,3-diyl group.

[0058] Among these, 1,4-phenylene group, naphthalene-2,6-diyl group, anthracene-1,4-diyl group, anthracene-1,5-diyl group, cyclohexane-1,4-diyl group, decalin-1,4-diyl group, decalin-2,6-diyl group, norbornane-2,3-diyl group, and tetracyclododecene-2,3-diyl group are preferred, and 1,4-phenylene group, naphthalene-2,6-diyl group, decalin-2,6-diyl group, and tetracyclododecene-2,3-diyl group are more preferred. The above groups may be used alone or in combination of two or more kinds.

[0059] Specific examples of such polybenzimidazoles include the following: Poly-2,2'-(m-phenylene)-5,5'-dibenzimidazole, Poly-2,2'-(diphenylene-2,2'')-5,5'-dibenzimidazole, Poly-2,2'-(diphenylene-4'',4'''')-5,5'-dibenzimidazole, Poly-2,2'-(1'',1'',3''-trimethylindanylene)-3'',5''-p-phenylene-5,5'-dibenzimidazole, 2,2'-(m-phenylene)-5,5'-dibenzoy midazole / 2,2'-(1'',1'',3''-trimethylindanylene)-3'',5''-p-phenylene-5,5'-dibenzimidazole copolymer, 2,2'-(m-phenylene)-5,5'-dibenzimidazole / 2,2'-(diphenylene-2'',2'''')-5,5'-dibenzimidazole copolymer, poly-2,2'-(furylene-2'',5'')-5,5'-dibenzimidazole, poly-2,2'-(naphthalene-1'',6'' ')-5,5'-dibenzimidazole, poly-2,2'-(naphthalene-2'',6'')-5,5'-dibenzimidazole, poly-2,2'-amylene-5,5'-dibenzimidazole, poly-2,2'-octamethylene-5,5'-dibenzimidazole, poly-2,2'-cyclohexenyl-5,5'-dibenzimidazole, poly-2,2'-(m-phenylene)-5,5'-di(benzimidazole) ether, poly-2,2'-(m-phenylene)-5,5'-di(benzimidazole) ether, poly-2,2'-(m-phenylene)-5,5'-di(benzimidazole) ether, poly-2,2'-(m-phenylene)-5,5'-di(benzimidazole) sulfide, poly-2,2'-(m-phenylene)-5,5'-di(benzimidazole) sulfone, poly-2,2'-(m-phenylene)-5,5'-di(benzimidazole) methane, poly-2,2'-(m-phenylene)-5,5'-di(benzimidazole) propane 2,2, and poly-ethylene-1,2,2,2''-(m-phenylene)-5,5'-di(benzimidazole) ethylene-1,2.

[0060] m is R 2 is an integer between 0 and 3. From the viewpoint of availability of raw materials and ease of production, R 2 is preferably not bulky. Therefore, m is preferably 0. When m is not 0, R 2is preferably an alkyl group having 1 to 3 carbon atoms, and m is preferably 1.

[0061] The above example is R 1 is a hydrogen atom, R 1 is preferably other than a hydrogen atom. In this case, the structure of the polybenzimidazole is represented by formula (1').

[0062] [ka]

[0063] In formula (1'), R 3 are each independently a substituent T selected from the group consisting of an alkyl group having 1 to 30 carbon atoms which may have a substituent, an aryl group having 6 to 40 carbon atoms which may have a substituent, an aralkyl group having 7 to 40 carbon atoms which may have a substituent, an alkenyl group having 2 to 30 carbon atoms which may have a substituent, an alkynyl group having 2 to 30 carbon atoms which may have a substituent, an arylalkenyl group having 7 to 40 carbon atoms which may have a substituent, an alkoxy group having 1 to 30 carbon atoms which may have a substituent, a halogen atom, a nitro group, an amino group, a cyano group, a carboxylic acid group, a thiol group, and a hydroxyl group, and the aryl group, the aralkyl group, the alkenyl group, the alkynyl group, and the arylalkenyl group are a substituent T which may contain an ether bond, a ketone bond, an ester bond, or a urethane bond. 2 , Y, Z, m, and n are defined as above.

[0064] R 3 Since R is not a hydrogen atom, the resin has the characteristics of excellent solubility in solvents and low water absorption due to the hydrogen bond suppression effect of hydrogen atoms and the intermolecular packing suppression effect. Therefore, a lithography film formed from the resin has excellent heat resistance and etching resistance. 3 may be a bridging group, i.e., R 3 They may react with each other to form a crosslinked structure, or R 3may react with a crosslinking agent described later to form a crosslinked structure between the resin and the crosslinking agent. Specific examples of the crosslinking group include an alkenyl group, an alkynyl group, and a group containing an epoxy group. Furthermore, the resin containing the structure represented by formula (1') is useful not only for lithography films, but also for injection molding, extrusion molding, and the like.

[0065] Polybenzimidazole can be obtained by reacting a tetraamino compound with a dicarboxylic acid, the corresponding dicarboxylic acid chloride, etc. In general, polybenzimidazole can be obtained by dehydrating and cyclizing polyaminoamide, which is one of the polybenzimidazole precursors obtained by reacting a tetraamino compound with a dicarboxylic acid, through heating or chemical treatment with phosphoric anhydride, base, carbodiimide compound, etc.

[0066] The tetraamino compound may include, for example, 3,3',4,4'-tetraaminobiphenyl, 2,3,5,6-tetraaminopyridine, 1,2,4,5-tetraaminobenzene, 3,3',4,4'-tetraaminodiphenylsulfone, 3,3',4,4'-tetraaminodiphenylether, 3,3',4,4'-tetraaminobenzophenone, 3,3',4,4'-tetraaminodiphenylmethane, and 3,3',4,4'-tetraaminodiphenyldimethylmethane. Specific examples of the tetraamino compound that can be preferably used are shown below.

[0067] [ka]

[0068] In the above formula, X represents -O-, -S-, -CH2-, -C(CH3)2-, -CO-, -SO2-, -C(CF3)2-, -CONH-, or -COO-. In this embodiment, tetraaminobiphenyl (TAB) is particularly preferred.

[0069] Examples of the dicarboxylic acid and dicarboxylic acid chloride include dicarboxylic acids such as terephthalic acid, isophthalic acid, diphenyl ether dicarboxylic acid, bis(carboxyphenyl)hexafluoropropane, biphenyl dicarboxylic acid, benzophenone dicarboxylic acid, and triphenyl dicarboxylic acid; and acid chloride compounds in which the carboxyl groups of dicarboxylic acids such as terephthalic acid, phthalic acid, maleic acid, cyclohexane dicarboxylic acid, 3-hydroxyphthalic acid, 5-norbornene-2,3-dicarboxylic acid, 1,2-dicarboxynaphthalene, 1,3-dicarboxynaphthalene, 1,4-dicarboxynaphthalene, 1,5-dicarboxynaphthalene, 1,6-dicarboxynaphthalene, 1,7-dicarboxynaphthalene, 1,8-dicarboxynaphthalene, 2,3-dicarboxynaphthalene, 2,6-dicarboxynaphthalene, and 2,7-dicarboxynaphthalene are converted into acid chlorides.

[0070] The resin containing the structure of formula (1') is R 1 The compound can be obtained by reacting a resin having a structure of formula (1) in which T is a hydrogen atom with a halogen compound THal (T is defined as above, and Hal is a halogen atom) in the presence of a base to replace the hydrogen atom with T. As the base, for example, sodium hydride or the like can be used. The reaction is preferably carried out in a solvent, and can be carried out at a temperature of about -20°C to 120°C using, for example, amides such as N,N-dimethylacetamide (DMAc) and N-methyl-2-pyrrolidone; cyclic aminoacetals such as dimethylimidazolidine and dimethylimidazolidinone (dimethylimidazolidine-dione); or the like. In this case, cesium carbonate or the like can also be used.

[0071] The lithography film-forming material of this embodiment can be applied to a wet process. In addition, the lithography film-forming material of this embodiment has an aromatic structure and a rigid benzimidazole skeleton, and therefore exhibits high heat resistance. Therefore, the temperature during baking can be set to a high temperature, and the carbon concentration in the film can be increased while suppressing film deterioration. As a result, a film with excellent etching resistance against oxygen plasma etching and the like can be formed. Furthermore, the lithography film-forming material of this embodiment has high solubility in organic solvents and high solubility in safe solvents despite having an aromatic structure. Furthermore, the lithography underlayer film made of the lithography film-forming composition of this embodiment described later has excellent embedding properties in step substrates and film flatness, and not only has good stability of product quality, but also has excellent adhesion to resist layers and resist intermediate layer film materials, so that an excellent resist pattern can be obtained.

[0072] [Film-forming composition for lithography] The composition for forming a film for lithography according to the present embodiment contains the film-forming material for lithography and a solvent. The film for lithography is, for example, an underlayer film for lithography. The underlayer film for lithography is a layer that exists between a substrate and a photoresist layer.

[0073] <Solvent> The solvent used in the film-forming composition for lithography of the present embodiment is not particularly limited as long as it dissolves the resin having the polybenzimidazole structure among the components in the composition, and any known solvent can be used as appropriate.

[0074] Specific examples of the solvent include those described in International Publication No. 2013 / 024779. These solvents may be used alone or in combination of two or more.

[0075] Among the above solvents, from the viewpoint of safety, aprotic polar solvents such as dimethyl sulfoxide, dimethylformamide, cyclohexanone, and anisole; polyhydric alcohol ethers such as propylene glycol monomethyl ether; and esters such as propylene glycol monomethyl ether acetate, ethyl lactate, and methyl hydroxyisobutyrate are particularly preferred.

[0076] The content of the solvent is not particularly limited, but from the viewpoints of solubility and film formation, it is preferably 25 to 9,900 parts by mass, more preferably 400 to 7,900 parts by mass, and even more preferably 900 to 4,900 parts by mass, relative to 100 parts by mass of the resin having a polybenzimidazole structure in the film-forming material for lithography.

[0077] <Acid generator> The lithography film-forming composition of the present embodiment may contain an acid generator as necessary from the viewpoint of further promoting the crosslinking reaction. As the acid generator, there are known ones that generate an acid by thermal decomposition, ones that generate an acid by light irradiation, etc., and any of them can be used. It is preferable to contain one or more acid generators that generate an acid directly or indirectly by irradiation with any radiation selected from visible light, ultraviolet light, excimer laser, electron beam, extreme ultraviolet light (EUV), X-rays, and ion beam. For example, those described in International Publication WO2013 / 024778 can be used. The acid generators can be used alone or in two or more kinds.

[0078] In the film-forming composition for lithography of the present embodiment, the content of the acid generator is not particularly limited, but is preferably 0 to 50 parts by mass, more preferably 0 to 40 parts by mass, based on 100 parts by mass of the resin having a polybenzimidazole structure in the film-forming material for lithography. By setting the content within the above-mentioned preferred range, the crosslinking reaction tends to be enhanced, and the occurrence of the mixing phenomenon with the resist layer tends to be suppressed.

[0079] <Basic compounds> Furthermore, the film-forming composition for lithography of the present embodiment may contain a basic compound from the viewpoint of improving storage stability, etc.

[0080] The basic compound plays a role of a quencher against the acid to prevent a small amount of acid generated from the acid generator from proceeding with a crosslinking reaction. Examples of such basic compounds include, but are not limited to, primary, secondary, or tertiary aliphatic amines, mixed amines, aromatic amines, heterocyclic amines, nitrogen-containing compounds having a carboxyl group, nitrogen-containing compounds having a sulfonyl group, nitrogen-containing compounds having a hydroxyl group, nitrogen-containing compounds having a hydroxyphenyl group, alcoholic nitrogen-containing compounds, amide derivatives, or imide derivatives, which are described in International Publication No. 2013-024779.

[0081] In the film-forming composition for lithography of the present embodiment, the content of the basic compound is not particularly limited, but is preferably 0 to 2 parts by mass, more preferably 0 to 1 part by mass, when the resin having a polybenzimidazole structure in the film-forming material for lithography is taken as 100 parts by mass. By setting the content within the above-mentioned preferred range, the storage stability tends to be improved without excessively impairing the crosslinking reaction.

[0082] Furthermore, the film-forming composition for lithography of the present embodiment may contain known additives, including, but not limited to, ultraviolet absorbers, antifoaming agents, colorants, pigments, nonionic surfactants, anionic surfactants, cationic surfactants, and the like.

[0083] <Crosslinking agent> The lithography film-forming composition of the present embodiment may contain a crosslinking agent as necessary from the viewpoint of suppressing intermixing, etc. The crosslinking agent that can be used in the present embodiment is not particularly limited, but for example, those described in International Publication No. 2013 / 024779 and International Publication No. 2018 / 016614 can be used. In the present embodiment, the crosslinking agent can be used alone or in combination of two or more kinds.

[0084] Specific examples of crosslinking agents that can be used in this embodiment include, but are not limited to, phenol compounds, epoxy compounds, cyanate compounds, amino compounds, benzoxazine compounds, acrylate compounds, melamine compounds, guanamine compounds, glycoluril compounds, urea compounds, isocyanate compounds, and azide compounds. These crosslinking agents can be used alone or in combination of two or more. Among these, benzoxazine compounds, epoxy compounds, or cyanate compounds are preferred, and benzoxazine compounds are more preferred from the viewpoint of improving etching resistance.

[0085] The phenol compound may be any known compound and is not particularly limited. From the viewpoints of heat resistance and solubility, however, aralkyl-type phenol resins are preferred.

[0086] The epoxy compound may be any known epoxy compound without any particular limitation. From the viewpoints of heat resistance and solubility, preferred are epoxy resins that are solid at room temperature, such as epoxy resins obtained from phenol aralkyl resins and biphenyl aralkyl resins.

[0087] The cyanate compound is not particularly limited as long as it has two or more cyanate groups in one molecule, and known cyanate compounds can be used. In this embodiment, preferred cyanate compounds include those having a structure in which the hydroxyl group of a compound having two or more hydroxyl groups in one molecule is replaced with a cyanate group. In addition, the cyanate compound is preferably one having an aromatic group, and can be preferably one having a structure in which the cyanate group is directly bonded to the aromatic group. Such cyanate compounds are not particularly limited, but examples thereof include those having a structure in which a hydroxyl group of bisphenol A, bisphenol F, bisphenol M, bisphenol P, bisphenol E, phenol novolac resin, cresol novolac resin, dicyclopentadiene novolac resin, tetramethylbisphenol F, bisphenol A novolac resin, brominated bisphenol A, brominated phenol novolac resin, trifunctional phenol, tetrafunctional phenol, naphthalene type phenol, biphenyl type phenol, phenol aralkyl resin, biphenyl aralkyl resin, naphthol aralkyl resin, dicyclopentadiene aralkyl resin, alicyclic phenol, phosphorus-containing phenol, etc. is substituted with a cyanate group. The cyanate compounds may be in the form of any one of monomer, oligomer, and resin.

[0088] The amino compound may be any known compound and is not particularly limited. However, from the viewpoints of heat resistance and availability of raw materials, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, and 4,4'-diaminodiphenyl ether are preferred.

[0089] The benzoxazine compound may be any known compound and is not particularly limited. However, Pd-type benzoxazines obtained from bifunctional diamines and monofunctional phenols are preferred from the viewpoint of heat resistance.

[0090] The melamine compound may be any known compound, and is not particularly limited. From the viewpoint of availability of raw materials, however, hexamethylolmelamine, hexamethoxymethylmelamine, a compound in which 1 to 6 methylol groups of hexamethylolmelamine are methoxymethylated, or a mixture thereof is preferred.

[0091] The guanamine compound may be any known compound and is not particularly limited. From the viewpoint of heat resistance, however, preferred are tetramethylolguanamine, tetramethoxymethylguanamine, and compounds in which 1 to 4 methylol groups of tetramethylolguanamine are methoxymethylated, or mixtures thereof.

[0092] The glycoluril compound may be any known compound and is not particularly limited. However, tetramethylol glycoluril and tetramethoxy glycoluril are preferred from the viewpoint of heat resistance and etching resistance.

[0093] The urea compound may be any known compound and is not particularly limited. However, tetramethylurea and tetramethoxymethylurea are preferred from the viewpoint of heat resistance.

[0094] In addition, in the present embodiment, from the viewpoint of improving crosslinking properties, a crosslinking agent having at least one allyl group may be used. Among them, allylphenols such as 2,2-bis(3-allyl-4-hydroxyphenyl)propane, 1,1,1,3,3,3-hexafluoro-2,2-bis(3-allyl-4-hydroxyphenyl)propane, bis(3-allyl-4-hydroxyphenyl)sulfone, bis(3-allyl-4-hydroxyphenyl)sulfide, and bis(3-allyl-4-hydroxyphenyl)ether are preferred.

[0095] The lithography film-forming material of the present embodiment can be formed by crosslinking and curing a resin having a polybenzimidazole structure alone or in combination with the crosslinking agent by a known method. Examples of the crosslinking method include heat curing and photocuring.

[0096] The content of the crosslinking agent is, for example, in the range of 0.1 to 100 parts by mass, preferably in the range of 1 to 50 parts by mass, and more preferably in the range of 1 to 30 parts by mass, from the viewpoints of heat resistance and solubility, relative to 100 parts by mass of the resin having a polybenzimidazole structure.

[0097] <Crosslinking accelerator> In the film-forming composition for lithography of the present embodiment, a crosslinking accelerator for accelerating the crosslinking and curing reaction can be used as necessary.

[0098] The crosslinking accelerator is not particularly limited as long as it accelerates crosslinking and curing reaction, and examples thereof include amines, imidazoles, organic phosphines, Lewis acids, etc. These crosslinking accelerators can be used alone or in combination of two or more. Among these, imidazoles or organic phosphines are preferred, and imidazoles are more preferred from the viewpoint of lowering the crosslinking temperature.

[0099] The crosslinking accelerator may be any known accelerator, and is not particularly limited, but examples thereof include those described in International Publication No. 2018 / 016614. From the viewpoints of heat resistance and curing acceleration, 2-methylimidazole, 2-phenylimidazole, and 2-ethyl-4-methylimidazole are particularly preferred.

[0100] The content of the crosslinking accelerator is usually preferably 0.1 to 10 parts by mass relative to 100 parts by mass of the total mass of the resin having a polybenzimidazole structure and the crosslinking agent, and from the viewpoints of ease of control and economic efficiency, it is more preferably 0.1 to 5 parts by mass, and even more preferably 0.1 to 3 parts by mass.

[0101] <Radical polymerization initiator> The lithography film-forming composition of the present embodiment may contain a radical polymerization initiator as necessary. The radical polymerization initiator may be a photopolymerization initiator that initiates radical polymerization by light, or a thermal polymerization initiator that initiates radical polymerization by heat. The radical polymerization initiator may be, for example, at least one selected from the group consisting of a ketone-based photopolymerization initiator, an organic peroxide-based polymerization initiator, and an azo-based polymerization initiator.

[0102] Such radical polymerization initiators are not particularly limited, and conventionally used ones can be appropriately adopted. For example, those described in International Publication No. 2018 / 016614 can be mentioned. Among these, dicumyl peroxide, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, and t-butylcumyl peroxide are particularly preferable from the viewpoint of raw material availability and storage stability.

[0103] As the radical polymerization initiator used in the present embodiment, one of these may be used alone or two or more of them may be used in combination, and other known polymerization initiators may also be used in combination.

[0104] The content of the radical polymerization initiator may be an amount stoichiometrically required for the mass of the resin having the polybenzimidazole structure, but is preferably 0.05 to 25 parts by mass, more preferably 0.1 to 10 parts by mass, when the resin having the polybenzimidazole structure is 100 parts by mass. When the content of the radical polymerization initiator is 0.05 parts by mass or more, the curing of the polybenzimidazole tends to be prevented from becoming insufficient, while when the content of the radical polymerization initiator is 25 parts by mass or less, the long-term storage stability of the film-forming material for lithography at room temperature tends to be prevented from being impaired.

[0105] <Film forming> The lithography film-forming composition of the present embodiment can be applied to a substrate, and then heated as necessary to evaporate the solvent, followed by heating or light irradiation to form a desired cured film. The lithography film-forming composition of the present embodiment can be applied by any method, and for example, methods such as spin coating, dip coating, flow coating, inkjet coating, spraying, bar coating, gravure coating, slit coating, roll coating, transfer printing, brush coating, blade coating, and air knife coating can be appropriately adopted.

[0106] The heating temperature of the film is not particularly limited for the purpose of evaporating the solvent, and can be, for example, 40 to 400°C. The heating method is not particularly limited, and for example, evaporation can be performed using a hot plate or oven under an appropriate atmosphere such as air, an inert gas such as nitrogen, or in a vacuum. The heating temperature and heating time can be selected according to the processing step of the target electronic device, and heating conditions can be selected such that the physical properties of the obtained film are compatible with the required characteristics of the electronic device. The conditions for light irradiation are also not particularly limited, and appropriate irradiation energy and irradiation time can be adopted depending on the film-forming material for lithography used.

[0107] Since etching resistance can be improved by controlling the C / O ratio in the lithography film, the film may be baked to achieve a preferred C / O ratio. For example, a higher ratio leads to higher resistance to oxygen plasma etching and etching with fluorine-based gas. The baking temperature is not particularly limited, but is usually in the range of 200°C to 1000°C. From the viewpoint of high carbonization and heat resistance of the film, it is preferably 300°C to 900°C, more preferably 400°C to 800°C, even more preferably 450°C to 700°C, and even more preferably 500°C to 700°C. The baking time is also not particularly limited, but is preferably in the range of 10 to 300 seconds.

[0108] [Method of forming underlayer film and pattern for lithography] The underlayer film for lithography of the present embodiment is formed using the film-forming composition for lithography of the present embodiment.

[0109] The pattern formation method of the present embodiment includes a step (A-1) of forming an underlayer film on a substrate using the film-forming composition for lithography of the present embodiment, a step (A-2) of forming at least one photoresist layer on the underlayer film, and, after the step (A-2), a step (A-3) of irradiating a predetermined region of the photoresist layer with radiation and performing development.

[0110] Another pattern formation method of this embodiment includes a step (B-1) of forming an underlayer film on a substrate using the film-forming composition for lithography of this embodiment, a step (B-2) of forming an intermediate layer film on the underlayer film using a resist intermediate layer film material containing silicon atoms, a step (B-3) of forming at least one photoresist layer on the intermediate layer film, and after the step (B-3), a step (B-4) of irradiating a predetermined region of the photoresist layer with radiation and developing it to form a resist pattern, and after the step (B-4), a step (B-5) of etching the intermediate layer film using the resist pattern as a mask, etching the underlayer film using the obtained intermediate layer film pattern as an etching mask, and etching the substrate using the obtained underlayer film pattern as an etching mask to form a pattern on the substrate.

[0111] The method for forming the underlayer film for lithography of this embodiment (hereinafter also simply referred to as "underlayer film") is not particularly limited as long as it is formed from the composition for forming a film for lithography of this embodiment, and a known method can be applied. For example, the composition for forming a film for lithography of this embodiment is applied to a substrate by a known coating method or printing method such as spin coating or screen printing, and then the organic solvent is removed by volatilization, etc., to form the underlayer film.

[0112] When forming the underlayer film, it is preferable to bake it in order to suppress the occurrence of the mixing phenomenon with the upper resist layer and promote the crosslinking reaction, or to achieve a preferable C / O ratio. The baking conditions are as described above. The thickness of the underlayer film can be appropriately selected according to the required performance, and is not particularly limited, but is usually preferably 30 to 20,000 nm, more preferably 50 to 15,000 nm, and even more preferably 50 to 1000 nm.

[0113] After forming an underlayer film on a substrate, it is preferable to form a silicon-containing resist layer thereon in the case of a two-layer process, or a single-layer resist made of a normal hydrocarbon thereon, and in the case of a three-layer process, a silicon-containing intermediate layer thereon, and further a silicon-free single-layer resist layer thereon. In this case, a known photoresist material can be used to form this resist layer.

[0114] As a silicon-containing resist material for a two-layer process, from the viewpoint of oxygen gas etching resistance, a positive photoresist material is preferably used which uses a silicon atom-containing polymer such as a polysilsesquioxane derivative or a vinylsilane derivative as a base polymer, and further contains an organic solvent, an acid generator, and if necessary, a basic compound, etc. Here, as the silicon atom-containing polymer, a known polymer used in this type of resist material can be used.

[0115] A polysilsesquioxane-based intermediate layer is preferably used as the silicon-containing intermediate layer for the three-layer process. By making the intermediate layer effective as an anti-reflection film, reflection tends to be effectively suppressed. For example, in a 193 nm exposure process, if a material containing many aromatic groups and having high substrate etching resistance is used as the underlayer film, the k value tends to be high and the substrate reflection tends to be high, but by suppressing reflection with the intermediate layer, the substrate reflection can be reduced to 0.5% or less. As an intermediate layer having such an anti-reflection effect, but not limited to the following, for 193 nm exposure, a polysilsesquioxane that is crosslinked by acid or heat and has a phenyl group or a light-absorbing group having a silicon-silicon bond introduced therein is preferably used.

[0116] An intermediate layer formed by a Chemical Vapour Deposition (CVD) method can also be used. As an intermediate layer produced by a CVD method that is highly effective as an anti-reflection film, for example, a SiON film is known, but is not limited to the following. In general, forming an intermediate layer by a wet process such as a spin coating method or screen printing has a simpler and more cost-effective advantage than the CVD method. The upper layer resist in the three-layer process may be either a positive type or a negative type, and the same resist as a commonly used single layer resist can be used.

[0117] Furthermore, the underlayer film of this embodiment can be used as an anti-reflection film for a normal single-layer resist or as an underlayer material for suppressing pattern collapse. Since the underlayer film of this embodiment has excellent etching resistance for underlayer processing, it can also be expected to function as a hard mask for underlayer processing.

[0118] When forming a resist layer using the photoresist material, a wet process such as spin coating or screen printing is preferably used, as in the case of forming the underlayer film. After applying the resist material by spin coating or the like, pre-baking is usually performed, and this pre-baking is preferably performed at 80 to 180° C. for 10 to 300 seconds. Thereafter, exposure is performed according to a conventional method, followed by post-exposure baking (PEB) and development to obtain a resist pattern. The thickness of the resist film is not particularly limited, but is generally preferably 30 to 500 nm, more preferably 50 to 400 nm.

[0119] The exposure light may be appropriately selected depending on the photoresist material used. In general, high energy rays having a wavelength of 300 nm or less, specifically, excimer lasers having wavelengths of 248 nm, 193 nm, and 157 nm, soft X-rays having wavelengths of 3 to 20 nm, electron beams, X-rays, and the like can be used.

[0120] The resist pattern formed by the above-mentioned method is prevented from collapsing by the underlayer film of this embodiment, and therefore, by using the underlayer film of this embodiment, a finer pattern can be obtained and the exposure dose required to obtain the resist pattern can be reduced.

[0121] Next, etching is performed using the obtained resist pattern as a mask. Gas etching is preferably used for etching the lower layer film in the two-layer process. Etching using oxygen gas is suitable for gas etching. In addition to oxygen gas, it is also possible to add inert gases such as He and Ar, or CO, CO2, NH3, SO2, N2, NO2, and H2 gases. Gas etching can also be performed using only CO, CO2, NH3, N2, NO2, and H2 gases without using oxygen gas. In particular, the latter gas is preferably used for sidewall protection to prevent undercutting of the pattern sidewall.

[0122] On the other hand, gas etching is also preferably used for etching the middle layer in the three-layer process. The gas etching can be the same as that described in the two-layer process. In particular, the processing of the middle layer in the three-layer process is preferably performed using a fluorocarbon-based gas and a resist pattern as a mask. Then, as described above, the processing of the lower layer film can be performed by, for example, performing oxygen gas etching using the middle layer pattern as a mask.

[0123] Here, when forming an inorganic hard mask intermediate layer film as the intermediate layer, a silicon oxide film, a silicon nitride film, or a silicon oxynitride film (SiON film) is formed by a CVD method, an ALD method, or the like. The method for forming the nitride film is not limited to the following, but for example, the method described in JP-A-2002-334869 (Patent Document 6) and WO2004 / 066377 (Patent Document 7) can be used. A photoresist film can be formed directly on such an intermediate layer film, but an organic anti-reflective coating (BARC) may be formed on the intermediate layer film by spin coating, and a photoresist film may be formed on the organic anti-reflective coating (BARC).

[0124] As the intermediate layer, a polysilsesquioxane-based intermediate layer is also preferably used. By making the resist intermediate layer film have an effect as an anti-reflection film, reflection tends to be effectively suppressed. The specific material of the polysilsesquioxane-based intermediate layer is not limited to the following, but for example, those described in JP-A-2007-226170 (Patent Document 8) and JP-A-2007-226204 (Patent Document 9) can be used.

[0125] The next etching of the substrate can also be performed by a conventional method, for example, if the substrate is SiO2 or SiN, etching can be performed mainly with fluorocarbon-based gas, and if it is p-Si, Al, or W, etching can be performed mainly with chlorine- or bromine-based gas. When etching the substrate with fluorocarbon-based gas, the silicon-containing resist of the two-layer resist process and the silicon-containing intermediate layer of the three-layer process are stripped at the same time as the substrate is processed. On the other hand, when the substrate is etched with chlorine- or bromine-based gas, the silicon-containing resist layer or the silicon-containing intermediate layer is stripped separately, and generally, dry etching stripping with fluorocarbon-based gas is performed after the substrate is processed.

[0126] The underlayer film of this embodiment is characterized by its excellent etching resistance to these substrates. The substrate can be appropriately selected from known ones and is not particularly limited, but examples thereof include Si, α-Si, p-Si, SiO2, SiN, SiON, W, TiN, Al, etc. The substrate may be a laminate having a film to be processed (substrate to be processed) on a base material (support). Examples of such a film to be processed include various low-k films such as Si, SiO2, SiON, SiN, p-Si, α-Si, W, W-Si, Al, Cu, Al-Si, and their stopper films, and the like, and a film made of a material different from that of the base material (support) is usually used. The thickness of the substrate or film to be processed is not particularly limited, but is usually preferably about 50 to 1,000,000 nm, more preferably 75 to 500,000 nm.

[0127] [Permanent resist film] A resist permanent film can also be prepared using the lithography film-forming composition of this embodiment. The resist permanent film formed by applying the composition to a substrate or the like is suitable as a permanent film that remains in the final product after forming a resist pattern as necessary. Specific examples of permanent films are not particularly limited, but include, for example, in the semiconductor device field, solder resist, packaging material, underfill material, package adhesive layer of circuit elements, and adhesive layer between integrated circuit elements and circuit boards, and in the thin display field, thin film transistor protective film, liquid crystal color filter protective film, black matrix, spacer, etc. In particular, the permanent film has the excellent advantage of being excellent in heat resistance and moisture resistance, and is less susceptible to contamination by sublimation components. In particular, in display materials, it is a material that combines high sensitivity, high heat resistance, and moisture absorption reliability with little image quality deterioration due to important contamination.

[0128] When the composition is used for a permanent resist film, in addition to the curing agent, various additives such as other resins, surfactants, dyes, fillers, crosslinking agents, and dissolution promoters can be added as necessary, and the composition can be dissolved in an organic solvent to form a composition for a permanent resist film.

[0129] The composition for the permanent resist film can be prepared by blending the above-mentioned components and mixing them using a stirrer, etc. When a filler or pigment is used, the composition for the permanent resist film can be prepared by dispersing or mixing them using a dispersing device such as a dissolver, a homogenizer, or a three-roll mill.

[0130] [Method for purifying film-forming materials for lithography] The lithographic film-forming material can be purified by washing with an acidic aqueous solution. The purification method includes a step of dissolving the lithographic film-forming material in an organic solvent that is not miscible with water to obtain an organic phase, contacting the organic phase with an acidic aqueous solution to perform an extraction treatment (first extraction step), thereby transferring the metal content contained in the organic phase containing the lithographic film-forming material and the organic solvent to the aqueous phase, and then separating the organic phase from the aqueous phase. The purification can significantly reduce the content of various metals in the lithographic film-forming material of the present invention.

[0131] The organic solvent that is not arbitrarily miscible with water is usually an organic solvent classified as a non-water-soluble solvent. The organic solvent is not particularly limited, but is preferably an organic solvent that can be safely applied to the semiconductor manufacturing process. The amount of the organic solvent used is usually about 1 to 100 times by mass relative to the compound used.

[0132] Specific examples of the organic solvent to be used include those described in International Publication No. 2015 / 080240. Among these, toluene, 2-heptanone, cyclohexanone, cyclopentanone, methyl isobutyl ketone, propylene glycol monomethyl ether acetate, ethyl acetate, etc. are preferred, and cyclohexanone and propylene glycol monomethyl ether acetate are particularly preferred. These organic solvents can be used alone or in combination of two or more.

[0133] The acidic aqueous solution is appropriately selected from among aqueous solutions in which a generally known organic or inorganic compound is dissolved in water. For example, those described in International Publication No. 2015 / 080240 can be mentioned. These acidic aqueous solutions can be used alone or in combination of two or more. Examples of the acidic aqueous solution include mineral acid aqueous solutions and organic acid aqueous solutions. Examples of the mineral acid aqueous solution include an aqueous solution containing one or more selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid. Examples of the organic acid aqueous solution include an aqueous solution containing one or more selected from the group consisting of acetic acid, propionic acid, oxalic acid, malonic acid, succinic acid, fumaric acid, maleic acid, tartaric acid, citric acid, methanesulfonic acid, phenolsulfonic acid, p-toluenesulfonic acid, and trifluoroacetic acid. In addition, as the acidic aqueous solution, an aqueous solution of sulfuric acid, nitric acid, and a carboxylic acid such as acetic acid, oxalic acid, tartaric acid, or citric acid is preferable, and an aqueous solution of sulfuric acid, oxalic acid, tartaric acid, or citric acid is more preferable, and an aqueous solution of oxalic acid is particularly preferable. It is considered that polycarboxylic acids such as oxalic acid, tartaric acid, and citric acid coordinate with metal ions and generate a chelating effect, so that more metals can be removed. In addition, the water used here is preferably one with a low metal content, such as ion-exchanged water, in line with the object of the present invention.

[0134] The pH of the acidic aqueous solution is not particularly limited, but if the acidity of the aqueous solution is too high, it may adversely affect the compound or resin used, which is not preferable. The pH range is usually about 0 to 5, and more preferably about pH 0 to 3.

[0135] The amount of the acidic aqueous solution used is not particularly limited, but if the amount is too small, it is necessary to perform extraction many times to remove the metal, and conversely, if the amount of the aqueous solution is too large, the total amount of the solution becomes large, which may cause problems in operation. The amount of the aqueous solution used is usually 10 to 200 parts by mass, preferably 20 to 100 parts by mass, based on the solution of the film-forming material for lithography.

[0136] The metal components can be extracted by contacting the acidic aqueous solution with a solution containing a film-forming material for lithography and an organic solvent that is arbitrarily immiscible with water.

[0137] The temperature during the extraction treatment is usually 20 to 90°C, preferably in the range of 30 to 80°C. The extraction operation is carried out, for example, by mixing thoroughly by stirring or the like, and then allowing to stand. As a result, metals contained in the solution containing the compound to be used and the organic solvent are transferred to the aqueous phase. This operation also reduces the acidity of the solution, making it possible to suppress deterioration of the compound to be used.

[0138] After the extraction treatment, the organic phase containing the compound and the organic solvent to be used is separated from the aqueous phase, and the organic phase is recovered by decantation or the like. The time for standing is not particularly limited, but if the time for standing is too short, the separation of the organic phase and the aqueous phase becomes poor, which is not preferable. Usually, the time for standing is 1 minute or more, more preferably 10 minutes or more, and even more preferably 30 minutes or more. In addition, the extraction treatment may be performed only once, but it is also effective to repeat the operations of mixing, standing, and separation several times.

[0139] When such an extraction treatment is carried out using an acidic aqueous solution, it is preferable to subject the organic phase containing the organic solvent extracted and recovered from the aqueous solution to a further extraction treatment with water (second extraction step). The extraction operation is carried out by thoroughly mixing the mixture by stirring or the like and then leaving it to stand. The resulting solution is separated into an organic phase and an aqueous phase, and the organic phase is recovered by decantation or the like. In addition, the water used here is preferably one with a low metal content, such as ion-exchanged water, in line with the object of the present invention. The extraction treatment may be carried out only once, but it is also effective to repeat the operations of mixing, leaving it to stand, and separating several times. In addition, the ratio of both used in the extraction treatment, and the conditions such as temperature and time are not particularly limited, but may be the same as in the case of the contact treatment with the acidic aqueous solution.

[0140] The organic phase thus obtained, which contains the lithographic film-forming material and the organic solvent, contains water, but the water can be easily removed by performing an operation such as distillation under reduced pressure. In addition, the concentration of the compound can be adjusted to any desired concentration by adding an organic solvent, if necessary.

[0141] Only the film-forming material for lithography can be obtained from the organic phase by using a known method such as removal under reduced pressure, separation by reprecipitation, or a combination thereof. If necessary, known treatments such as concentration, filtration, centrifugation, drying, etc. can be performed. EXAMPLES

[0142] The present invention will be described in more detail below with reference to Examples, Production Examples, and Comparative Examples, but the present invention is not limited to these Examples in any way.

[0143] [Molecular weight] The molecular weight Mn and Mw / Mn of the synthesized resin were measured by carrying out gel permeation chromatography (GPC) analysis under the following conditions to determine the molecular weight in terms of polystyrene. Equipment: Shodex GPC-101 (Showa Denko Co., Ltd.) Column: KF-80M x 3 Eluent:DMF 1mL / min Temperature: 40℃

[0144] [Heat resistance evaluation] Using an EXSTAR6000TG-DTA device manufactured by SII Nano Technology, approximately 5 mg of the resin having a polybenzimidazole structure obtained in the synthesis example below was placed in an aluminum non-sealed container, and the heat loss was measured by heating it to 500°C at a heating rate of 10°C / min in a nitrogen gas (100 ml / min) flow. The results are shown in Table 1. From a practical standpoint, the following A or B rating is preferable. Ratings of A or B indicate high heat resistance and can be applied to high-temperature baking. The rating criteria are as follows: A: Thermal weight loss at 400℃ is less than 10% B: Thermal weight loss at 400℃ is 10% to 25% C: Thermal weight loss at 400℃ is more than 25%

[0145] [Evaluation of solubility] Dimethyl sulfoxide (DMSO) and the resin having a polybenzimidazole structure obtained in the following synthesis example were charged into a 50 ml screw bottle and stirred with a magnetic stirrer at 23°C for 1 hour, after which the amount dissolved in the mixed solvent was measured and the results were evaluated according to the following criteria. The results are shown in Table 1. From a practical standpoint, the following evaluation of A or B is preferable. Evaluation of A or B indicates high storage stability in a solution state and is fully applicable to semiconductor microfabrication processes. A: 10% by mass or more B: 5% by mass or more and less than 10% by mass C: Less than 5% by mass

[0146] <Synthesis Example 1> 3,3',4,4'-Tetraaminobiphenyl (Kanto Chemical Co., Ltd.; 3.14 g, 10 mmol) was added to polyphosphoric acid (50 g) in a 200 mL eggplant flask, and the mixture was stirred in an oil bath at 160 °C for 3 h to dissolve tetraaminobiphenyl in polyphosphoric acid. Isophthalic acid (Mitsubishi Gas Chemical Co., Ltd.; 1.46 g, 10 mmol) was added to the homogeneous solution, and the oil bath was heated to 200 °C and stirred for 24 h. The reaction mixture was then cooled to 80 °C (or to room temperature if possible), and 100 mL of distilled water was carefully added. This mixture was stirred at room temperature for 1 h, then suction filtered, and the residue was washed with distilled water (20 mL x 5), after which 200 mL of saturated aqueous sodium bicarbonate solution was added and the mixture was stirred at room temperature for 6 h. The residue was washed with distilled water (50 mL x 10) and acetone (20 mL x 10) while suction filtering, and the residue was vacuum dried at 100°C for 24 hours to obtain a beige solid polybenzimidazole represented by the following formula in a yield of 98% (3.15 g). The molecular weight of the obtained resin was Mn: 11800, and the polydispersity was Mw / Mn: 2.9.

[0147] <Synthesis Example 1-1> In a 100 mL eggplant flask, polybenzimidazole PBI-n (771 mg, 2.5 mmol) obtained in Synthesis Example 1 was added with dry DMF (50 mL) to prepare a homogeneous solution. Cesium carbonate (2.44 g, 7.5 mmol) was added to the solution, and after stirring at room temperature for 30 min, benzyl bromide (1.03 g, 6 mmol) was added dropwise over 10 min. The reaction mixture was stirred at room temperature for 12 h, and then dropped into 200 mL of methanol to obtain a fibrous precipitate. The precipitate was washed with methanol (50 mL x 10) while suction filtering, and the residue was vacuum dried at 60 ° C for 24 h to obtain a beige solid benzyl-protected polybenzimidazole represented by the following formula in a yield of 97% (1.18 g). The molecular weight of the obtained resin was Mn: 18690, and the polydispersity was Mw / Mn: 2.8.

[0148] <Synthesis Example 1-2> In a 100 mL eggplant flask, polybenzimidazole PBI-n (771 mg, 2.5 mmol) obtained in Synthesis Example 1 was added with dry DMF (50 mL) to prepare a homogeneous solution. Cesium carbonate (2.44 g, 7.5 mmol) was added to the solution, and after stirring at room temperature, bromoethanol (0.32 g, 6 mmol) was added dropwise. The reaction mixture was stirred at room temperature for 6 hours, and then dropped into 200 mL of methanol to obtain a fibrous precipitate. The precipitate was washed with methanol (50 mL x 10) while suction filtering, and the residue was vacuum dried at 60 ° C for 24 hours to obtain hydroxyethyl-protected polybenzimidazole represented by the following formula in a yield of 95% (1.18 g). The molecular weight of the obtained resin was Mn: 13200, and the polydispersity was Mw / Mn: 2.9.

[0149] [ka]

[0150] <Synthesis Example 2> Polybenzimidazole represented by the following formula was obtained in a yield of 97% (3.49 g) under the same conditions as in Synthesis Example 1, except that the tetraaminobiphenyl in Synthesis Example 1 was changed to 3,3',4,4'-tetraaminooxydiphenyl (manufactured by Kanto Chemical Co., Ltd.). The molecular weight of the obtained resin was Mn: 5800, and the polydispersity was Mw / Mn: 2.2.

[0151] <Synthesis Example 2-1> A benzyl-protected polybenzimidazole (Bz-PBI-E) represented by the following formula was obtained in a yield of 96% under the same conditions as in Synthesis Example 1-1, except that PBI-E obtained in Synthesis Example 2 was used instead of PBI-n obtained in Synthesis Example 1. The molecular weight of the obtained resin was Mn: 9020, and the polydispersity index was Mw / Mn: 2.3.

[0152] <Synthesis Example 2-2> Hydroxyethyl-protected polybenzimidazole (Et-PBI-E) represented by the following formula was obtained in a yield of 94% under the same conditions as in Synthesis Example 1-2, except that PBI-E obtained in Synthesis Example 2 was used instead of PBI-n obtained in Synthesis Example 1. The molecular weight of the obtained resin was Mn: 7130, and the polydispersity index was Mw / Mn: 2.1.

[0153] [ka]

[0154] <Synthesis Example 3> A polybenzimidazole (PBI-S) represented by the following formula was obtained in a yield of 95% under the same conditions as in Synthesis Example 1, except that the tetraaminobiphenyl in Synthesis Example 1 was changed to 3,3',4,4'-tetraaminophenyl ether sulfone (manufactured by Kanto Chemical Co., Ltd.). The molecular weight of the obtained resin was Mn: 9300, and the polydispersity was Mw / Mn: 6.9.

[0155] <Synthesis Example 3-1> A benzyl-protected polybenzimidazole (Bz-PBI-S) represented by the following formula was obtained in a yield of 95% under the same conditions as in Synthesis Example 1-1, except that PBI-S obtained in Synthesis Example 3 was used instead of PBI-n obtained in Synthesis Example 1. The molecular weight of the obtained resin was Mn: 13,800, and the polydispersity index was Mw / Mn: 7.2.

[0156] <Synthesis Example 3-2> Hydroxyethyl-protected polybenzimidazole (Et-PBI-S) represented by the following formula was obtained in a yield of 94% under the same conditions as in Synthesis Example 1-2, except that PBI-S obtained in Synthesis Example 3 was used instead of PBI-n obtained in Synthesis Example 1. The molecular weight of the obtained resin was Mn: 11200, and the polydispersity index was Mw / Mn: 6.9.

[0157] [ka]

[0158] <Production Example 1> A four-neck flask with a capacity of 10 L and a bottom-removable capacity equipped with a Dimroth condenser, a thermometer, and a stirring blade was prepared. 1.09 kg (7 mol, manufactured by Mitsubishi Gas Chemical Co., Ltd.) of 1,5-dimethylnaphthalene, 2.1 kg of 40% by mass formalin aqueous solution (28 mol as formaldehyde, manufactured by Mitsubishi Gas Chemical Co., Ltd.), and 0.97 ml of 98% by mass sulfuric acid (manufactured by Kanto Chemical Co., Ltd.) were charged in this four-neck flask in a nitrogen gas flow, and the mixture was reacted for 7 hours while refluxing at 100°C under normal pressure. Then, 1.8 kg of ethylbenzene (manufactured by Wako Pure Chemical Industries, Ltd., special grade reagent) was added as a dilution solvent to the reaction solution, and after standing, the aqueous phase of the lower phase was removed. Furthermore, the mixture was neutralized and washed with water, and ethylbenzene and unreacted 1,5-dimethylnaphthalene were distilled off under reduced pressure to obtain 1.25 kg of dimethylnaphthalene formaldehyde resin as a light brown solid. The molecular weight of the obtained dimethylnaphthalene formaldehyde resin was as follows: number average molecular weight (Mn): 562, weight average molecular weight (Mw): 1168, and dispersity (Mw / Mn): 2.08.

[0159] Next, a four-neck flask with an internal volume of 0.5 L equipped with a Dimroth condenser, a thermometer, and a stirring blade was prepared. Into this four-neck flask, 100 g (0.51 mol) of the dimethylnaphthalene formaldehyde resin obtained as described above and 0.05 g of paratoluenesulfonic acid were charged under a nitrogen gas flow, and the temperature was raised to 190° C. and heated for 2 hours, and then stirred. Then, 52.0 g (0.36 mol) of 1-naphthol was added, and the temperature was raised to 220° C. and reacted for 2 hours. After dilution with a solvent, neutralization and washing with water were performed, and the solvent was removed under reduced pressure to obtain 126.1 g of a modified resin (CR-1) as a black-brown solid. The obtained resin (CR-1) had Mn: 885, Mw: 2220, and Mw / Mn: 2.51.

[0160] [Table 1]

[0161] <Examples 1 to 15, Comparative Examples 1 to 2> Using the resin obtained in the synthesis examples and DMSO, lithography film-forming compositions having the compositions shown in Table 2 were prepared (Examples 1 to 15). Furthermore, using the resin obtained in Production Example 1, comparative lithography film-forming compositions were prepared (Comparative Examples 1 and 2). The phenylaralkyl type epoxy resin (NC-3000-L: manufactured by Nippon Kayaku Co., Ltd.) used as the crosslinking agent is represented by the following formula.

[0162] [ka]

[0163] Next, the lithography film-forming compositions of Examples 1 to 15 and Comparative Examples 1 and 2 were spin-coated on a silicon substrate, and then baked at 240°C for 60 seconds and then at 400°C for 120 seconds to prepare an underlayer film with a thickness of 200 nm. The film thickness reduction rate (%) was calculated from the difference in film thickness before and after baking at 400°C to evaluate the film heat resistance of each underlayer film. Then, the etching resistance was evaluated under the conditions shown below. The results are shown in Table 2.

[0164] [Film thickness measurement] The thickness of the resin film obtained from the film-forming composition for lithography was measured by an interference film thickness meter "OPTM-A1" (manufactured by Otsuka Electronics Co., Ltd.).

[0165] [Evaluation of film heat resistance] The evaluation criteria were as follows. S: Film thickness reduction rate before and after 400℃ baking ≦10% A: Film thickness reduction rate before and after 400℃ baking ≦15% B: Film thickness reduction rate before and after 400℃ baking ≦20% C: Film thickness reduction rate before and after 400℃ baking > 20%

[0166] [Etching test] Etching equipment: Samco International RIE-10NR Output: 50W Pressure: 4Pa Time: 2 minutes Etching Gas CF4 gas flow rate: O2 gas flow rate = 5:15 (sccm)

[0167] [Evaluation of etching resistance] The etching resistance was evaluated according to the following procedure. First, a novolac underlayer film was prepared under the same conditions as in Example 1, except that a novolac (PSM4357 manufactured by Gun-ei Chemical Co., Ltd.) was used instead of the lithography film-forming material in Example 1, and the drying temperature was set to 110° C. Then, the above-mentioned etching test was performed on this novolac underlayer film, and the etching rate was measured. Next, the etching test was carried out in the same manner as above for the underlayer films of Examples 1 to 15 and Comparative Examples 1 and 2, and the etching rates were measured. The etching resistance was evaluated according to the following evaluation criteria, based on the etching rate of the novolac underlayer film: From a practical viewpoint, the following S rating is particularly preferable, and A and B ratings are more preferable.

[0168] S: Etching rate is less than -30% compared to the underlayer of novolac A: The etching rate is between -30% and -20% compared to the novolac underlayer. B: The etching rate is -20% or more and less than -10% compared to the underlayer film of novolac. C: The etching rate is -10% or more and 0% or less compared to the underlayer film of novolac.

[0169] [Table 2]

[0170] <Example 16> The lithography film-forming composition obtained in Example 1 was applied onto a SiO2 substrate having a thickness of 300 nm, and baked at 240°C for 60 seconds and then at 400°C for 120 seconds to form an underlayer film having a thickness of 70 nm. An ArF resist solution was applied onto this underlayer film, and baked at 130°C for 60 seconds to form a photoresist layer having a thickness of 140 nm. The ArF resist solution was prepared by blending 5 parts by mass of a compound of the following formula (22), 1 part by mass of triphenylsulfonium nonafluoromethanesulfonate, 2 parts by mass of tributylamine, and 92 parts by mass of PGMEA.

[0171] The compound of the following formula (22) was prepared as follows. That is, 4.15 g of 2-methyl-2-methacryloyloxyadamantane, 3.00 g of methacryloyloxy-γ-butyrolactone, 2.08 g of 3-hydroxy-1-adamantyl methacrylate, and 0.38 g of azobisisobutyronitrile were dissolved in 80 mL of tetrahydrofuran to obtain a solution. This solution was polymerized for 22 hours under a nitrogen atmosphere while maintaining the reaction temperature at 63° C., and then the reaction solution was dropped into 400 mL of n-hexane. The resin thus produced was coagulated and purified, and the white powder thus produced was filtered and dried overnight at 40° C. under reduced pressure to obtain a compound represented by the following formula.

[0172] [ka]

[0173] In the above formula, 40, 40, and 20 represent the ratios of the respective structural units, and do not indicate that the polymer is a block copolymer.

[0174] The photoresist layer was then exposed to light using an electron beam lithography system (ELS-7500, 50 keV, manufactured by Elionix), baked at 115°C for 90 seconds (PEB), and developed with a 2.38% by mass aqueous solution of tetramethylammonium hydroxide (TMAH) for 60 seconds to obtain a positive resist pattern. The evaluation results are shown in Table 3.

[0175] <Example 17> A positive resist pattern was obtained in the same manner as in Example 16, except that the composition for forming an underlayer film for lithography in Example 2 was used instead of the composition for forming an underlayer film for lithography in Example 1. The evaluation results are shown in Table 3.

[0176] <Example 18> A positive resist pattern was obtained in the same manner as in Example 16, except that the composition for forming an underlayer film for lithography in Example 3 was used instead of the composition for forming an underlayer film for lithography in Example 1. The evaluation results are shown in Table 3.

[0177] <Comparative Example 3> Except for not forming an underlayer film, a photoresist layer was formed directly on a SiO2 substrate in the same manner as in Example 16, and a positive resist pattern was obtained. The evaluation results are shown in Table 3.

[0178] [evaluation] For each of Examples 16 to 18 and Comparative Example 3, the shapes of the obtained resist patterns of 55 nmL / S (1:1) and 80 nmL / S (1:1) were observed using an electron microscope (S-4800) manufactured by Hitachi, Ltd. Regarding the shape of the resist pattern after development, those without pattern collapse and with good rectangularity were evaluated as good, and those without were evaluated as bad. Furthermore, as a result of the observation, the minimum line width without pattern collapse and with good rectangularity was used as an index of evaluation as resolution. Furthermore, the minimum amount of electron beam energy capable of drawing a good pattern shape was used as an index of evaluation as sensitivity.

[0179] [Table 3]

[0180] As is clear from Table 3, it was confirmed that Examples 16 to 18 using the film-forming composition for lithography of this embodiment were significantly superior in both resolution and sensitivity compared to Comparative Example 3. In addition, it was confirmed that the resist pattern shape after development was free of pattern collapse and had good rectangularity. From the difference in the resist pattern shape after development, it was shown that the underlayer films of Examples 16 to 18 obtained from the film-forming composition for lithography of Examples 1 to 3 have good adhesion to the resist material.

[0181] <Example B1> The film-forming composition for lithography prepared in Example 1 was spin-coated on a silicon substrate, and the film was formed and the solvent was removed by baking at 150° C. for 60 seconds. Then, heat resistance was evaluated using a lamp annealing furnace as described below.

[0182] <Examples B2 to B15, Comparative Examples B1 to B2> Except for changing the composition for forming a film for lithography used to the composition shown in Table 4, the heat resistance evaluation was carried out in the same manner as in Example B1.

[0183] [High temperature heat resistance evaluation of cured film] The substrate on which the film was formed was heated at 450°C in a nitrogen atmosphere, and the film thickness change rate was determined for 4 and 10 minutes after the start of heating. Heating was continued at 550°C in a nitrogen atmosphere, and the film thickness change rate was determined for 4 and 10 minutes after the start of heating. These film thickness change rates were evaluated as an index of the heat resistance of the cured film. The film thickness before and after the heat resistance test was measured with an interference film thickness meter, and the film thickness change rate (percentage %) based on the film thickness before the heat resistance test treatment was taken as the film thickness variation value. The results are shown in Table 4.

[0184] [Table 4]

[0185] <Example C1> A 12-inch silicon wafer was subjected to thermal oxidation treatment to prepare a substrate having a silicon oxide film, and a resin film having a thickness of 100 nm was formed thereon in the same manner using the film-forming composition for lithography of Example 1. A silicon oxide film and a SiN film were formed on the resin film as described below, and the PE-CVD film formability was evaluated.

[0186] <Examples C2 to C15 and Comparative Examples C1 to C2> Except for changing the composition for forming a film for lithography used to the composition shown in Table 5, a film was formed in the same manner as in Example C1, and evaluated.

[0187] [Silicon oxide film evaluation] A silicon oxide film with a thickness of 70 nm was formed on the resin film using a film forming device TELINDY (manufactured by Tokyo Electron Ltd.) and TEOS (tetraethylsiloxane) as a raw material at a substrate temperature of 300° C. A defect inspection was performed on the wafer with the cured film laminated with this silicon oxide film using a KLA-Tencor SP-5, and the number of defects in the formed oxide film was evaluated using the number of defects of 21 nm or more as an index. A Number of defects ≦ 20 B 20 pieces < Number of defects ≦ 50 pieces C 50 pieces < Number of defects ≦ 100 pieces D 100 pieces < Number of defects ≦ 1000 pieces E 1000 pieces < Number of defects ≦ 5000 pieces F 5000 pieces < Number of defects

[0188] [SiN film evaluation] Using the same method as above, a hardened film was formed on a substrate having a silicon oxide film thermally oxidized to a thickness of 100 nm on a 12-inch silicon wafer, and a SiN film with a thickness of 40 nm, a refractive index of 1.94, and a film stress of -54 MPa was formed at a substrate temperature of 350°C using SiN4 (monosilane) and ammonia as raw materials using a film forming device TELINDY (manufactured by Tokyo Electron Co., Ltd.). The wafer with the hardened film laminated with the SiN film was subjected to defect inspection using a KLA-Tencor SP-5, and the number of defects in the formed oxide film was evaluated using the number of defects of 21 nm or more as an index as described above. These results are shown in Table 5.

[0189] [Table 5]

[0190] The silicon oxide films or SiN films formed on the resin films of Examples C1 to C15 had 50 or less defects measuring 21 nm or more (rating B or higher), which was shown to be less than the number of defects in Comparative Examples C1 and C2.

[0191] <Example D1> A 12-inch silicon wafer was subjected to a thermal oxidation treatment to form a silicon oxide film, and a resin film of 100 nm thickness was formed on the substrate using the lithography film-forming composition solution of Example 1 in the same manner as in Example 1. The resin film was further subjected to an annealing treatment by heating at 600°C for 4 minutes using a hot plate capable of high-temperature treatment in a nitrogen atmosphere, to produce a wafer on which an annealed resin film was laminated. The substrate was subjected to an etching evaluation as described below.

[0192] [Etching evaluation after high-temperature treatment] The substrate was etched using a TELIUS etching device (Tokyo Electron Co., Ltd.) under the conditions of using CF4 / Ar and Cl2 / Ar as etching gases, and the etching rate was evaluated. The etching rate was evaluated by using a 200 nm thick resin film made by annealing SU8 (Nippon Kayaku Co., Ltd.) at 250°C for 1 minute as a reference, and calculating the speed ratio of the etching rate to SU8 as a relative value.

[0193] <Examples D2 to D15, Comparative Examples D1 to D2> Except for changing the film-forming composition for lithography used to the composition shown in Table 6, the etching evaluation after the high-temperature treatment was carried out in the same manner as in Example D1.

[0194] [Table 6]

[0195] Example E1: Acid purification of Et-PBI-n resin In a 1000mL four-neck flask (bottom-opening type), 150g of a solution (10% by mass) of the Et-PBI-n resin obtained in Synthesis Example 1-2 dissolved in cyclohexanone (CHN) was charged and heated to 80°C while stirring. Next, 37.5g of an aqueous oxalic acid solution (pH 1.3) was added, stirred for 5 minutes, and then allowed to stand for 30 minutes. As a result, the system separated into an oil phase and an aqueous phase, and the aqueous phase was removed. After repeating this operation once, 37.5g of ultrapure water was charged into the obtained oil phase, stirred for 5 minutes, and then allowed to stand for 30 minutes, and the aqueous phase was removed. After repeating this operation three times, the flask was heated to 80°C while reducing the pressure inside to 200hPa or less, thereby concentrating and distilling off the residual water and CHN. Then, the solution was diluted with EL grade CHN (a reagent manufactured by Kanto Chemical Co., Ltd.) and the concentration was adjusted to 10% by mass to obtain a CHN solution of Et-PBI-n resin with reduced metal content. The resin solution was filtered under a condition of 0.5 MPa using a UPE filter having a nominal pore size of 3 nm manufactured by Nippon Entegris Co., Ltd. A solution sample was obtained by using the solution sample to evaluate etching defects in a laminated film as described below.

[0196] [Evaluation of etching defects in multilayer films] The quality of the laminated film was evaluated by purifying the composition. That is, the composition for forming a film for lithography was used to form a film on a wafer, and the film was etched to reflect the properties of the film on the substrate, and then defects were evaluated. Specifically, the evaluation was performed as follows. (Si oxide film formed substrate) A 12-inch silicon wafer was subjected to thermal oxidation treatment to obtain a substrate having a silicon oxide film with a thickness of 100 nm. The solution of the purified lithography film-forming composition was spin-coated on the substrate to a thickness of 100 nm, and then baked at 150°C for 1 minute, followed by baking at 350°C for 1 minute to produce a laminated substrate in which a lithography underlayer film was laminated on the thermally oxidized silicon. The underlayer film for lithography was etched using a TELIUS (Tokyo Electron) etching device under the conditions of CF4 / O2 / Ar to expose the substrate on the oxide film surface. Further, an etching process was performed under the conditions of etching the oxide film by 100 nm with a gas composition ratio of CF4 / Ar to produce an etched wafer. The number of defects of 19 nm or more in the etched wafer was measured using a defect inspection device SP5 (KLA-tencor). The evaluation criteria were as described above.

[0197] (SiN film forming substrate) On a substrate having a silicon oxide film thermally oxidized to a thickness of 100 nm on a 12-inch silicon wafer, a SiN film having a thickness of 40 nm, a refractive index of 1.94, and a film stress of -54 MPa was formed at a substrate temperature of 350°C using a film forming device TELINDY (manufactured by Tokyo Electron Co., Ltd.) and SiN4 (monosilane) and ammonia as raw materials, to produce a substrate with a laminated SiN film. A lithography underlayer film was formed on the substrate in the same manner as above, and an etching process was performed under the same conditions to produce an etched wafer. The number of defects of 19 nm or more in the etched wafer was measured using a defect inspection device SP5 (manufactured by KLA-tencor Co., Ltd.). The evaluation criteria were as described above.

[0198] Example E2: Purification by passing through a filter In a class 1000 clean booth, 500 g of a 10% by mass solution of the Et-PBI-n resin obtained in Synthesis Example 1-2 dissolved in cyclohexanone (CHN) was charged into a 1000 mL capacity four-neck flask (bottom-opening type). After the air inside the flask was removed under reduced pressure, nitrogen gas was introduced to return to atmospheric pressure, and the oxygen concentration inside was adjusted to less than 1% while aerating nitrogen gas at 100 mL per minute, and then the mixture was heated to 30°C while stirring. The above solution was extracted from the bottom-opening valve, and passed through a nylon hollow fiber membrane filter (manufactured by Kitz Microfilter Co., Ltd., product name: Polyfix Nylon Series) with a nominal pore size of 0.01 μm via a pressure-resistant tube made of fluororesin, so that the filtration pressure was 0.5 MPa, and pressure filtration was performed. A diaphragm pump was used for passing the liquid, and the flow rate was set to 100 mL per minute. The filtered resin solution was diluted with EL grade CHN (a reagent manufactured by Kanto Chemical Co., Ltd.) and the concentration was adjusted to 10% by mass to obtain a CHN solution of Et-PBI-n resin with reduced metal content. The resin solution was filtered under 0.5 MPa using a UPE filter with a nominal pore size of 3 nm manufactured by Nippon Entegris Co., Ltd. to obtain a solution sample. Using the solution sample, an etching defect evaluation was performed on the laminated film. The oxygen concentration was measured using an oxygen concentration meter "OM-25MF10" manufactured by AS ONE Corporation (same below).

[0199] <Example E3> A filter line was constructed by connecting IONKLEEN manufactured by Nippon Pall Corporation, a nylon filter manufactured by Nippon Pall Corporation, and a UPE filter with a nominal pore size of 3 nm manufactured by Nippon Integris Corporation in series in this order. Pressure filtration was performed in the same manner as in Example E2, except that the filter line was used instead of a 0.01 μm nylon hollow fiber membrane filter. A CHN solution of Et-PBI-n resin with reduced metal content was obtained by diluting with EL grade CHN (a reagent manufactured by Kanto Chemical Co., Ltd.) and adjusting the concentration to 10 mass %. The solution was pressure-filtered with a UPE filter with a nominal pore size of 3 nm manufactured by Nippon Integris Co., Ltd. under a filtration pressure of 0.5 MPa to obtain a solution sample. The solution sample was used to evaluate etching defects in a laminated film.

[0200] <Example E4> The solution sample prepared in Example E1 was further filtered under pressure using the filter line prepared in Example E3 at a filtration pressure of 0.5 MPa to obtain a solution sample, which was used to evaluate etching defects in a laminated film.

[0201] <Example E5> The Et-PBI-E prepared in Synthesis Example 2-2 was purified in the same manner as in Example E1 to obtain a solution sample. Using the solution sample, an etching defect evaluation was performed on the laminated film.

[0202] <Example E6> The Et-PBI-S prepared in Synthesis Example 3-2 was purified in the same manner as in Example E1 to obtain a solution sample, which was used to evaluate etching defects in a laminated film.

[0203] [Table 7] [Industrial Applicability]

[0204] The lithography film-forming material of this embodiment has relatively high heat resistance, relatively high solvent solubility, excellent embedding properties in step substrates and film flatness, and is applicable to wet processes. Therefore, the lithography film-forming composition containing the lithography film-forming material can be widely and effectively used in various applications requiring these properties. In particular, the present invention can be particularly effectively used in the fields of lithography underlayer films and multilayer resist underlayer films.

Claims

1. forming an underlayer film on a substrate using a film-forming composition for lithography, the film-forming composition comprising a film-forming material for lithography containing a resin having a polybenzimidazole structure represented by the following formula (1) and a solvent; forming at least one photoresist layer on the underlayer film; and exposing predetermined areas of the photoresist layer to radiation and developing; Including, Equation (1) is as follows: 【Chemistry 1】 (In formula (1), Y and Z each represent a single bond; a divalent linking group containing a chalcogen atom; and a divalent linking group derived from a compound selected from the group consisting of an aromatic compound, a linear, branched or cyclic aliphatic compound, and a heterocyclic compound, Each R 1 is independently an aralkyl group having 7 to 40 carbon atoms or an alkyl group having 1 to 30 carbon atoms to which a hydroxyl group is bonded; R 2 is a substituent T selected from the group consisting of an alkyl group having 1 to 30 carbon atoms which may have a substituent, an aryl group having 6 to 40 carbon atoms which may have a substituent, an aralkyl group having 7 to 40 carbon atoms which may have a substituent, an alkenyl group having 2 to 30 carbon atoms which may have a substituent, an alkynyl group having 2 to 30 carbon atoms which may have a substituent, an arylalkenyl group having 7 to 40 carbon atoms which may have a substituent, an alkoxy group having 1 to 30 carbon atoms which may have a substituent, a halogen atom, a nitro group, an amino group, a cyano group, a carboxylic acid group, a thiol group and a hydroxyl group, and the aryl group, the aralkyl group, the arkenyl group, the alkynyl group, the arylalkenyl group, the alkynyl group, the arylalkenyl group, the alkoxy group, the alkynyl group, the arylalkenyl ... an arylalkenyl group, an alkynyl group, or an arylalkenyl group is a substituent T which may contain an ether bond, a ketone bond, an ester bond, or a urethane bond; m is 0 or 1; n is an integer from 1 to 10,000. A method for forming a resist pattern.

2. forming an underlayer film on a substrate using a film-forming composition for lithography, the film-forming composition comprising a film-forming material for lithography containing a resin having a polybenzimidazole structure represented by the following formula (1) and a solvent; forming an intermediate layer film on the underlayer film using a resist intermediate layer film material containing silicon atoms; forming at least one photoresist layer on the intermediate layer film; irradiating predetermined areas of the photoresist layer with radiation and developing to form a resist pattern; a step of etching the intermediate layer film using the resist pattern as a mask; a step of etching the underlayer film using the obtained intermediate layer film pattern as an etching mask; and a step of forming a pattern on the substrate by etching the substrate using the obtained underlayer film pattern as an etching mask; Including, Equation (1) is as follows: 【Chemistry 1】 (In formula (1), Y and Z each represent a single bond; a divalent linking group containing a chalcogen atom; and a divalent linking group derived from a compound selected from the group consisting of an aromatic compound, a linear, branched or cyclic aliphatic compound, and a heterocyclic compound, Each R 1 is independently an aralkyl group having 7 to 40 carbon atoms or an alkyl group having 1 to 30 carbon atoms to which a hydroxyl group is bonded; R 2 is a substituent T selected from the group consisting of an alkyl group having 1 to 30 carbon atoms which may have a substituent, an aryl group having 6 to 40 carbon atoms which may have a substituent, an aralkyl group having 7 to 40 carbon atoms which may have a substituent, an alkenyl group having 2 to 30 carbon atoms which may have a substituent, an alkynyl group having 2 to 30 carbon atoms which may have a substituent, an arylalkenyl group having 7 to 40 carbon atoms which may have a substituent, an alkoxy group having 1 to 30 carbon atoms which may have a substituent, a halogen atom, a nitro group, an amino group, a cyano group, a carboxylic acid group, a thiol group and a hydroxyl group, and the aryl group, the aralkyl group, the arkenyl group, the alkynyl group, the arylalkenyl group, the alkynyl group, the arylalkenyl group, the alkoxy group, the alkynyl group, the arylalkenyl ... an arylalkenyl group, an alkynyl group, or an arylalkenyl group is a substituent T which may contain an ether bond, a ketone bond, an ester bond, or a urethane bond; m is 0 or 1; n is an integer from 1 to 10,000. Pattern formation method.

3. The Y is a single bond, —O—, —S—, or —CH 2 -, -C(CH 3 ) 2 -, -CO-, -SO 2 -, -C(CF 3 ) 2 The method according to claim 1 or 2, wherein the radical is -, -CONH- or -COO-.

4. The method of claim 3 , wherein Y is a single bond.

5. The method according to any one of claims 1 to 4, wherein the film-forming composition for lithography further contains a crosslinking agent, a crosslinking promoter, a radical polymerization initiator, an acid generator, or a combination thereof.

Citation Information

Patent Citations

  • Organic composite high-temperature proton exchange membrane and preparation method thereof

    CN106803598A

  • Pattern forming method

    JP1986248039A

  • Positive photoresist composition

    JP1994027657A

  • Method and device for forming silicon nitride film, and method for preprocessing of cleaning thereof

    JP2002334869A

  • Base layer film forming material for multilayer resist process, and wiring formation method using the same

    JP2004177668A